2018
DOI: 10.4236/ajps.2018.97114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Air Temperature and Carbon Dioxide Levels on Dry Season Irrigated Rice Productivity in Bangladesh

Abstract: Agricultural productivity is affected by air temperature and CO 2 concentration. The relationships among grain yields of dry season irrigated rice (Boro) varieties (BRRI dhan28, BRRI dhan29 and BRRI dhan58) with increased temperatures and CO 2 concentrations were investigated for futuristic crop management in six regions of Bangladesh using CERES-Rice model (DSSATv4.6). Maximum and minimum temperature increase rates considered were 0˚C, +1˚C, +2˚C, +3˚C and +4˚C and CO 2 concentrations were ambient (380), 421,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Biswas et al [ 68 ] also reported that rice growth duration and yield decrease with a delay in planting date. The delay in transplanting exposes the flowering stage of rice to extremely high temperature, which reduces the yield significantly [ 69 , 70 ]. So, the variation in actual yield between fields of the same variety can be attributed to some extent to variation in transplanting date, although the ANOVA test did not show a significant difference ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biswas et al [ 68 ] also reported that rice growth duration and yield decrease with a delay in planting date. The delay in transplanting exposes the flowering stage of rice to extremely high temperature, which reduces the yield significantly [ 69 , 70 ]. So, the variation in actual yield between fields of the same variety can be attributed to some extent to variation in transplanting date, although the ANOVA test did not show a significant difference ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growth duration of Boro rice decreased by 6.4 days per 1°C temperature rise. Maniruzzaman et al [24] showed similar findings of 7.45 days' growth duration reduction of BRRI dhan28 for 1°C temperature rise. Mahmud [37] also reported 7-8 days' growth duration reduction per 1°C temperature rise for BR23 cultivar.…”
Section: Temperature Effect On Growth Duration and Grain Yieldmentioning
confidence: 57%
“…Rising temperature accelerates the crop growth and development process, resulting in shortening the growth duration of irrigated rice [38]. However, growth duration contributes directly to the yield, but shorter life span due to rising temperature may affect the production in the future [24].…”
Section: Temperature Effect On Growth Duration and Grain Yieldmentioning
confidence: 99%
See 2 more Smart Citations